Opinions on the preparation of history teachers presented in the press of "Wiadomości Historyczno-Dydaktyczne" (1933-1939) - Iwona Czarnecka (Studia z Teorii Wychowania)
In the journal "Wiadomości Historyczno-Dydaktyczne" published in 1933-1939 historians' opinions were printed. They were aboyt preparation for the work of history teacher. From this preparation the level of implementation of the new curricula for this subject depended. The authors of the articles noticed the disadvantages of education history teachers at the time. They pointed to wrong solutions, postulated various changes which, in their opinion, were hepl and enable proper education of staff for general and secondary eduacation. At he same time, they developed proposals for these changes themselves and presented them in the journal.